Zebrafish as a Model of Neurodevelopmental Disorders. (1st October 2020) - de Abreu, Murilo S.; Genario, Rafael; Giacomini, Ana C.V.V.; Demin, Konstantin A.; Lakstygal, Anton M.; Amstislavskaya, Tamara G.; Fontana, Barbara Dotto; Parker, Matthew O.; Kalueff, Allan V.
Highlights: Neurodevelopmental disorders are life-long, serious human brain illnesses. Animal models are a valuable tool for studying neurodevelopmental disorders. The zebrafish emerges as a promising model organism to probe these disorders and their mechanisms. Here, we discuss zebrafish models and phenotypes relevant to neurodevelopmental disorders. Abstract: Neurodevelopmental disorders (NDDs) caused by aberrant brain growth and development are life-long, debilitating illnesses that markedly impair the quality of life. Animal models are a valuable tool for studying NDD pathobiology and therapies. Mounting evidence suggests the zebrafish ( Danio rerio ) as a useful model organism to study NDDs, possessing both high physiological homology to humans and sensitivity to pharmacological and genetic manipulations. Here, we summarize experimental models of NDDs in zebrafish and highlight the growing translational significance of zebrafish NDD-related phenotypes. We also emphasize the need in further development of zebrafish models of NDDs to improve our understanding of their pathogenesis and therapeutic treatments.